Recent Advances in Nanomaterial Probes for Optical Biothiol Sensing: A Review. (4th March 2018) - Tsogas, George Z.; Kappi, Foteini A.; Vlessidis, Athanasios G.; Giokas, Dimosthenis L.
ABSTRACT: The determination of biological aminothiols (mainly cysteine, homocysteine, and glutathione) is an important tool in the clinical diagnosis of many disorders and diseases. Therefore, the development of new chemical sensors and probes has attracted considerable attention. Nanomaterials have a profound role in this endeavor since they offer some unique advantages such as lower cost, faster analysis times, and ease of operation compared to classic instrumental techniques such as liquid chromatography and capillary electrophoresis. In this review, we provide a focused outline on the most recent evolvements in optical biothiol sensing using nanomaterials. The most important reaction mechanisms and detection strategies are summarized and compared in terms of their sensitivity and selectivity against various biothiol species. Critical fields for future research and challenges are discussed and elucidated.